Mobile Europe: The Theory and Practice of Free Movement in the EU - Recchi, Ettore (Palgrave Macmillan, 2020)
With a particular focus on their integration paths, political participation and identifications, this book draws on large cross-national surveys of this specific population carried out between 2004 and 2012, as well as in-depth interviews and aggregate statistical data from a plethora of sources.